Vingårdar i Sverige! : farligt för miljön? - Wirell, Fredrik (SLU/Dept. of Soil and Environment, 2012)
The future climate of Sweden is expected to become warmer in the future. This would be beneficial for vineyards and may lead to a greater area being allocated for wine production. The environmental impact concerning eutrophication from Swedish vineyards has not been evaluated before. In this study nutrient balances are constructed for four Swedish vineyards with the goal to estimate the out and in flows of nutrient in the systems for the year 2010. Interviews with focus on farming practices undertaken during the year are conducted with the farmers. The results of these interviews are used as the fundament of the nutrient balance. A literature study is undertaken as to gain information on the vine nutrient allocation during the year. This obtained information together with the result of the interview is then used to calculate the in and out flow of nutrients. Three of the vineyards showed a surplus of nutrients while the fourth showed a deficit. The surplus is a sign that there may be excess nutrients applied to the system, these nutrients may leach out to close by watercourses and, disturbing their ecosystems. When comparing the surpluses from the three vineyards to balances resulting from alternative land use (arable land and pastures) the vineyard surpluses are relatively small. Fertilizing strategies on Swedish vineyards can therefore not be said to be causing environmental damage in an eutrophication perspective.